Reattributing Heracl. Pont. F 102 Schütr. - Pavlova, Anastasiia (Hyperboreus, 2022)
The article aims at reattributing the fragment 102 (Schütrumpf) by Heraclides of Pontus, which was traditionally considered together with fragment 101, both being attributed to Heraclides’ Λύσεις Ὁμηρικαί (Solutions of Homeric Problems). Both fragments deal with Telemachus’ speech in the second book of the Odyssey, but while the first one (F 101) discusses an inconsistency in Homer’s poem, as required by the genre of λύσεις, the second (F 102) discusses the Telemachus’ speech from the rhetorical point of view, which seems to be much more appropriate for a rhetorical treatise. Heraclides’ catalogue includes only one rhetorical work Περὶ τοῦ ῥητορεύειν ἢ Προταγόρας, probably a dialogue. Although not a single fragment of this dialogue survives, testimonies of Protagoras’ studies in rhetorics and literary criticism suggest that the F 102 by Heraclides originates from Περὶ τοῦ ῥητορεύειν ἢ Προταγόρας.